Impulsive people have a compulsion for immediate gratification—certain or uncertain - Białaszek, Wojciech; Gaik, Maciej; McGoun, Elton; Zielonka, Piotr (Frontiers in Psychology, 2015)
Impulsivity has been defined as choosing the smaller more immediate reward over a larger more delayed reward. The purpose of this research was to gain a deeper understanding of the mental processes involved in the decision making. We examined participants’ rates of delay discounting and probability discounting to determine their correlation with time-probability trade-offs. To establish the time-probability trade-off rate, participants adjusted a risky, immediate payoff to a delayed, certain payoff. In effect, this yielded a probability equivalent of waiting time. We found a strong, positive correlation between delay discount rates and the time-probability trade-offs. This means that impulsive people have a compulsion for immediate gratification, independent of whether the immediate reward is certain or uncertain. Thus, they seem not to be concerned with risk but rather with time.